Is Blood Alcohol Level a Good Predictor for Injury Severity Outcomes in Motor Vehicle Crash Victims? - Bikaramjit Mann; Ediriweera Desapriya; Takeo Fujiwara; Ian Pike (Emergency Medicine International)
Experimental studies in animals suggest that alcohol may influence pathophysiologic response to injury mechanisms. However, biological evidence for the alcohol-injury severity relationship provides conflicting results. The purpose of our retrospective cross-sectional study in 2,323 people was to assess whether blood alcohol level (BAC) adversely influences injury severity in victims of motor vehicle collisions (MVCs). We found no difference in mortality OR 1.09 (0.73–1.62), or length of hospital stay, and a trend for lower ISS score was found in the high-alcohol group (P=0.052). Furthermore, the high-alcohol group demonstrated a lower adjusted rate of severe head injury OR 0.65 (0.48–0.87), chest injury OR 0.58 (0.42–0.80), and serious extremity injury OR 0.10 (0.01–0.76). The findings of our study do not demonstrate a dose-response relationship between alcohol consumption and injury severity in MVCs. This study implies that higher BAC may lead to less severe injuries, without impacting mortality or length of hospital stay, however, further research is required to elucidate the nature of this relationship.